Economic Integration of the Visegrad Four and Ukraine in the Context of Historical Narratives and Global Challenges - Savelyev, Yevhen; Lyzun, Mariia; Kuryliak, Vitalina; Lishchynskyy, Ihor (European Journal of Sustainable Development, 2021)
The article reveals the historical preconditions for the development of economic integration of Ukraine and the Visegrad Four from the standpoint of challenges relevant to the region of Central and Eastern Europe. The co-existence of the Rus’ people (ancient Ukrainians) with the Czech, Polish, Hungarian and Slovak ethnic groups is outlined, highlighting the significant events. They are presented in the context of building good neighbourly relations through overcoming contradictions. V4 is considered as an association of new political and economic order within the framework of European integration processes. The routes of economic integration of Ukraine and V4 have been assessed, revealing that this process is mainly limited to import operations and excludes real sector of the economy. A concept is developed for the V4+UA economic space, specifying the creation of a regionally integrated machine industry with fragmented production within a global-scale network and high added value.